2009
DOI: 10.1017/s1041610209990676
|View full text |Cite
|
Sign up to set email alerts
|

Is the Clock Drawing Test a screening tool for the diagnosis of mild cognitive impairment? A systematic review

Abstract: CDT should not be used for MCI-screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 41 publications
3
43
1
5
Order By: Relevance
“…In more discrete conditions, however, the results are inconsistent. Our results suggest worse performance of MCI patients than NC, but a review of similar studies found negative results 30 . The second predic tor of CDT performance in our study may be related to the integration of different cognitive domains necessary for task performance.…”
Section: Discussioncontrasting
confidence: 55%
“…In more discrete conditions, however, the results are inconsistent. Our results suggest worse performance of MCI patients than NC, but a review of similar studies found negative results 30 . The second predic tor of CDT performance in our study may be related to the integration of different cognitive domains necessary for task performance.…”
Section: Discussioncontrasting
confidence: 55%
“…Moreover, the CDT requires different cognitive abilities including auditory and visual comprehension, concentration, visuospatial abilities, abstract conceptualization, and executive control (Shulman, 2000). However, the findings concerning the CDT's ability to differentiate between subjects with and without MCI are rather inconsistent (Lee et al, 2008;Pinto and Peters, 2009;Ehreke et al, 2010). For example, Yamamoto et al (2004) found that the CDT has utility to screen for MCI, whereas Lee et al (2008) did not recommend the use of the CDT as a screening instrument for MCI.…”
Section: Introductionmentioning
confidence: 99%
“…la prueba del dibujo del reloj (PDR), ha sido empleada para la detección de demencia, siendo de fácil y rápida administración, permite evaluar las siguientes habilidades cognitivas: comprensión auditiva, planeamiento, memoria visual, reconstrucción de una imagen gráfica, habilidades viso-espaciales, programación motora y ejecución, conocimiento numérico y concentración (15,18) ; pero no permite detectar deterioro cognitivo mínimo (DCM) (19) . Una revisión de Pinto et al, muestra diferentes formas de administrar la PDR, así como diferentes maneras de calificar la prueba (20) , cualitativa y cuantitativamente, siendo estas últimas mejor verificables y reproducibles.…”
Section: Introductionunclassified